Pengaruh Motivasi, Lingkungan Kerja Non Fisik dan Konflik Kerja terhadap Kepuasan Kerja Karyawan pada PT. Karya Sukses Usaha Mandiri - Lilis Evhelia Sihotang; Ananda Fitriani Dewi (Pusat Riset dan Inovasi Nasional, 2024)
The research was conducted to determine the influence of motivation, non-physical work environment and work conflict on employee job satisfaction at PT. Karya Sukses Usaha Mandiri. The data in the study were obtained through questionnaires, observations and interviews. The sampling technique used in this study is Nonprobability Sampling with a total sample technique. The results of the study show that 1. The results of the T test calculated for the work motivation variable of 5,336 > T-table 2,024 and the sig value of 0.000 < 0.025, namely work motivation had a significant effect on job satisfaction. 2. The results of the T test calculated on the non-physical work environment variable of 2,955 > t-table 2,024 and the sig value of 0.005 < 0.025, namely the non-physical work environment had a significant effect on job satisfaction. 3. The results of the T test calculated on the work conflict variable of 3,269 > t-table 2,024 and The SIG value is 0.002 < 0.025, namely work conflict has a significant effect on job satisfaction. The results of the determinant coefficient showed that work motivation, non-physical work environment and work conflict had an influence on the job satisfaction variabel of 49.7% while 50.3% was influenced by other variabels that were not studied in this research